(untitled) (Third Sector Social Economic Review, 2025)
This study empirically examines the long-term relationships between the domestic producer price index (PPI) in Türkiye and the Cost-Based Competitiveness Index (RGD), developed in 2025, the real effective exchange rate (REER), and the export quantity index (IME). The analysis utilizes a comprehensive sectoral panel dataset with quarterly frequency covering the period 2015–2025. Panel data econometric methods and the Johansen cointegration test are employed to thoroughly investigate the long-term dynamics among the variables. The results reveal that increases in cost-based competitiveness have a significant and negative long-term effect on the PPI, whereas increases in REER and IME exert a positive impact on PPI. The most notable contribution of the study is the empirical inclusion and application of the RGD index—used for the first time in the literature—in the analysis of price dynamics. In this way, the critical role of cost-oriented competition in ensuring price stability within the manufacturing sector is scientifically demonstrated. Additionally, the findings clarify the mechanisms through which exchange rate fluctuations and export performance create pressure on prices, providing a practical roadmap for industry representatives and policymakers. This research offers essential empirical evidence to guide policymakers in developing strategies aimed at enhancing price stability and international competitiveness in Türkiye.